FISH APARTMENT AS A SOLUTION FOR INCREASING FISH CATCH IN PACITAN WATER, EAST JAVA - Ledhyane Ika Harlyan; Syarifah Hikmah Julinda Sari; Defri Yona (Journal of Innovation and Applied Technology, 2017)
Fish apartment is a device used by fishermen for aggregating and locating their fish target. Problem arised from apartments managed by local fishermen locals are not as many that managed by fisherman andon. Besides, the fish apartment used is contructed by using toxic material (dioxin compound) which is caused several environmental problems. Therefore, creating community services by using fish apartment made from Plastic Polypropilen (PP) and controlled by community group, those problems are accomplished. This is beneficial for increasing community involvement for their environment through this joint activities to create fish apartment which later used for increasing fish catch in order to enhance public welfare.Methods used for this activity arranged as four stage. First, developing the Tawangsari community group (POKMASWAS Tawangsari) and Tawangsari business group (KUB Tawangsari). Second, generating workshop on designing and determining potential location of fish apartment. Third, producing fish apartment, and the last is setting fish apartment. The series of activities lasted in seven months from May to November 2016.